Eksistensi Radio: Tantangan dan Peluang di Era Digital dan Post-Pandemic COVID-19 (Sebuah Pendekatan dengan Metode Tinjauan Literatur Sistematik) - Sinabariba, Santa Cicilia (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
Radio became an actor in the development of digitalization of technology, which began with the arrival of the internet. The existence of radio is questioned during the emergence of internet-based technology, one of which is due to the view that sees radio as something old-fashioned and difficult to adapt to changing times. However, the fact is that radio today still continues to survive even during the COVID-19 pandemic, radio listeners globally and in Indonesia have increased. This is a turning point in the rise of radio listeners. This paper looks at how radio can maintain its existence and what the radio industry should do in the midst of the digital era and after the COVID-19 pandemic by using a systematic literature review (SLR) with the Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.  This approach is carried out by looking at, analyzing and comparing a number of studies from international journals that have been published and related to the topic discussed. The results show that radio still has a future, both public and community radio. Radio still has a great opportunity to continue to grow. The study used in this paper shows that radio still has a bright future if it emphasizes the quality of programs and the affordability of media technology.